2002
DOI: 10.1096/fj.01-0504com
|View full text |Cite
|
Sign up to set email alerts
|

Cells in human postmortem brain tissue slices remain alive for several weeks in culture

Abstract: Animal models for human neurological and psychiatric diseases only partially mimic the underlying pathogenic processes. Therefore, we investigated the potential use of cultured postmortem brain tissue from adult neurological patients and controls. The present study shows that human brain tissue slices obtained by autopsy within 8 h after death can be maintained in vitro for extended periods (up to 78 days) and can be manipulated experimentally. We report for the first time that 1) neurons and glia in such cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 35 publications
7
86
1
1
Order By: Relevance
“…We validated these protocols in postmortem tissues and have successfully used them to study other signaling mechanisms (Wang and Friedman, 2001;Hahn et al, 2006). The viability of the postmortem FCX used in this study was illustrated by the presence of high-affinity choline uptake and ChAT activity, which resonates with a previous demonstration that postmortem brain slices (up to 8 h in ambient temperature) remain alive for several weeks in culture (Verwer et al, 2002). Although the degree to which the result of this protocol corresponds to in vivo measurements remains unclear, these postmortem brain function protocols can provide valuable information on functional status of the disease brains and effects of drugs on specific brain activities.…”
Section: Discussionsupporting
confidence: 71%
“…We validated these protocols in postmortem tissues and have successfully used them to study other signaling mechanisms (Wang and Friedman, 2001;Hahn et al, 2006). The viability of the postmortem FCX used in this study was illustrated by the presence of high-affinity choline uptake and ChAT activity, which resonates with a previous demonstration that postmortem brain slices (up to 8 h in ambient temperature) remain alive for several weeks in culture (Verwer et al, 2002). Although the degree to which the result of this protocol corresponds to in vivo measurements remains unclear, these postmortem brain function protocols can provide valuable information on functional status of the disease brains and effects of drugs on specific brain activities.…”
Section: Discussionsupporting
confidence: 71%
“…We tested such responses using an ex vivo stimulation protocol with which we previously showed that nicotinic, neuregulin-1, and NMDA signaling is intact in human postmortem tissue obtained 6-11 hours after death on average (73,74). Such findings are not surprising, since neurons in thick brain sections from postmortem N and AD cases with PMIs up to 8 hours can be kept alive in culture media at least 3 weeks without significant loss in numbers, morphology, or measures of viability (75). To validate the ex vivo protocol for insulin signaling studies on postmortem tissue, we tested it first on normal brain tissue.…”
Section: Resultsmentioning
confidence: 97%
“…This model is therefore ideal for weeklong studies, which correspond to the time that the glial architecture is best preserved. This is not as long as prior studies using postmortem brain tissue, but it should be realized that the tissue in our study is obtained intra-operatively and thus subjected to surgical manipulation (Verwer et al 2002). Also, because these tissues are obtained intra-operatively from human patients, it makes comparative analysis difficult because these tissues are obtained from various cortical regions and from different patients with different underlying pathologies.…”
Section: Advantages and Limitations Of Our Ex Vivo Modelmentioning
confidence: 99%
“…Since this initial study, there have been several more that have used these methods to evaluate rodent-based brain tissue models (Cavaliere et al 2006;Holopainen 2005;Holtkamp et al 2005;Tanaka et al 1994;Valster et al 2005). Humanbased brain tissue models have been primarily limited to fetal tissue (Jakovcevski and Zecevic 2005;Lyman et al 1992;Tenenbaum et al 2004) and cadaveric tissue (Bsibsi et al 2006;Verwer et al 2002). Brain slices obtained from living human patients have been described infrequently, and the preservation of the cytoarchitecture in these explants is not known (Jung et al 1999;Jung et al 2002).…”
Section: Establishment Of An Ex Vivo Human Model To Study Human Diseasementioning
confidence: 99%